A kinome siRNA screen identifies HGS as a potential target for liver cancers with oncogenic mutations in CTNNB1. Issue 1 (December 2015) - Canal, Frédéric; Anthony, Elodie; Lescure, Aurianne; Del Nery, Elaine; Camonis, Jacques; Perez, Franck; Ragazzon, Bruno; Perret, Christine
Abstract Background Aberrant activation of the Wnt/β-catenin pathway is a major and frequent event in liver cancer, but inhibition of oncogenic β-catenin signaling has proven challenging. The identification of genes that are synthetically lethal in β-catenin-activated cancer cells would provide new targets for therapeutic drug design. Methods We transfected the parental HuH6 hepatoblastoma cell line with a doxycycline-inducible shRNA againstCTNNB1 (gene coding for β-catenin) to obtain an isogenic cell line pair with or without aberrant β-catenin signaling. Using this hepatoblastoma isogenic cell line pair, we performed a human kinome-wide siRNA screen to identify synthetic lethal interactions with oncogenicCTNNB1 . The phenotypic readouts of the screen were cell proliferation, cell cycle arrest and apoptosis, which were assessed by image-based analysis. In addition, apoptosis was assessed by flow cytometric experiments and immunoblotting. The potential synthetic lethal relationship between candidates genes identified in the screen and oncogenicCTNNB1 was also investigated in a different cellular context, a colorectal HCT116 isogenic cell line pair. Results We first determined the experimental conditions that led to the efficient expression of shRNA againstCTNNB1 and maximal reduction of β-catenin signaling activity in response to doxycycline treatment. Following high throughput screening in which 687 genes coding for kinases and proteins related to kinases (such as pseudokinases and phosphatases) were targeted, we identified 52 genes required for HuH6 survival. The silencing of five of these genes selectively impaired the viability of HuH6 cells with high β-catenin signaling:HGS, STRADA, FES, BRAF andPKMYT1 . Among these candidates, HGS depletion had the strongest inhibitory effect on cell growth and led to apoptosis specifically in HuH6 with high β-catenin activity, while HuH6 with low β-catenin activity were spared. In addition, HGS was identified as a potential synthetic lethal partner of oncogenicCTNNB1 in the HCT116 colorectal isogenic cell line pair. Conclusions These results demonstrate the existence of crosstalk between β-catenin signaling andHGS . Importantly, HGS depletion specifically affected cells with uncontrolled β-catenin signaling activity in two different types of cancer (Hepatoblastoma HuH6 and colorectal HCT116), and thus may represent a new potential target for novel therapeutic strategies in liver and colorectal cancer.